Efektivitas Komunikasi Audio Bagi Penyandang Disabilitas Tunanetra dalam Bidang Agama Islam - Lusi Kurnia Agustin; Rojabi Azharghany (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the effectiveness of audio communication media in teaching Islamic Religious Education to visually impaired students at a Special Needs School (SLB). Using a qualitative approach and a constructivist paradigm, the research focuses on the use of audio media such as the YMusic application and WhatsApp voice notes to support the learning process. Data were collected through observations, in-depth interviews, and documentation involving teachers and students at SLB Negeri Kraksaan. The results show that audio media play a vital role in enhancing students' imagination, social sensitivity, and reasoning abilities. The use of stories about prophets and interactive voice communication enables visually impaired students to actively receive, interpret, and internalize religious material. This approach not only strengthens cognitive understanding but also supports emotional and social growth, making the learning experience more holistic. Additionally, audio media help build students’ self-confidence by providing an inclusive and flexible communication space where they can express their thoughts without fear. However, significant challenges exist, such as differences in students’ learning needs, limitations in managing engaging and relevant audio content, and social stigma affecting students' confidence. Teachers must be creative and adaptive in addressing these differences to ensure effective learning. A key unexpected finding is that audio media function beyond just a learning aid; they serve as a symbolic medium to build religious meaning and personal identity for visually impaired students. This media creates a safe and empowering learning environment, encouraging active participation and confidence in religious education. This study is limited by its scope, focusing on a single school with a limited number of subjects. Further research is recommended to explore audio media more broadly, develop interactive digital audio tools, and use quantitative or mixed methods to objectively measure long-term impacts.